In-Line Estimation of the Magnetization Curve of Steel Strips in a Continuous Induction Furnace. Issue 2 (2020) - Jadachowski, L.; Roetzer, F.; Steinboeck, A.; Kugi, A.
Abstract: An in-line parameter estimation strategy for continuous inductive heating of ferromagnetic steel strips is developed and investigated. During strip processing in a longitudinal flux induction furnace, the parameters of the magnetization curve (B-H curve) of the strip material are identified by a moving horizon estimator (MHE). The estimator uses a tailored 2D spatial-temporal model of the furnace which takes into account both the thermal and the electromagnetic subsystem. Other model parameters are identified in a scenario, where the magnetization curve of the strip is known. For model validation, the simulated strip temperature at the furnace exit is compared with measurements. To approximate the solution of the nonlinear Maxwell equations, the effective magnetization approach is applied. Here, a sophisticated hysteretic magnetization model is avoided in favor of the computing time, while magnetic saturation effects in the strip are still captured. The developed MHE is validated in a simulation scenario based on a strip with a known magnetization curve.